2018
DOI: 10.1016/j.appet.2018.04.014
|View full text |Cite|
|
Sign up to set email alerts
|

How people's food disgust sensitivity shapes their eating and food behaviour

Abstract: Although research regarding disgust has increased enormously in the last decades, to date there is a lack of published research about the influence of food disgust on various food-related behaviours. Our study aimed to provide an understanding about the relationships between food disgust sensitivity and eating preferences (texture-based food rejection), habits (variety seeking), and behaviours (picky eating) as well as food waste frequency. Additionally, sociodemographic characteristics associated with food di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 62 publications
6
62
2
Order By: Relevance
“…Thus, using nanotechnology to prolong food shelf life, for example, will probably not be accepted by consumers. Given that a recently published study found a positive association between food disgust sensitivity and food waste frequency (Egolf, Siegrist, & Hartmann, ), the present finding is disappointing.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Thus, using nanotechnology to prolong food shelf life, for example, will probably not be accepted by consumers. Given that a recently published study found a positive association between food disgust sensitivity and food waste frequency (Egolf, Siegrist, & Hartmann, ), the present finding is disappointing.…”
Section: Discussioncontrasting
confidence: 79%
“…Average scores were calculated across all items ( M = 3.58, SD = 0.97, Cronbach's α = 0.78). The scale seems to be a reliable and valid measurement tool to predict various eating and food behaviors (Ammann, Hartmann, & Siegrist, ; Egolf, Siegrist, & Hartmann, ).…”
Section: Methodsmentioning
confidence: 99%
“…Current work in this area has focused on the association between selective eating and sensory sensitivity (e.g., Naish & Harris, ; Zucker et al, ). However, a number of recent studies have shown a strong correlation between disgust sensitivity and selective eating, food neophobia, and food‐related textural aversions (Egolf, Siegrist, & Hartmann, ; Hartmann & Siegrist, ; Kauer, Pelchat, Rozin, & Zickgraf, ). These studies have shown that disgust sensitivity is positively correlated with picky eating and textural aversions in a cross sectional sample of healthy adults (Egolf et al, ; Kauer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of recent studies have shown a strong correlation between disgust sensitivity and selective eating, food neophobia, and food‐related textural aversions (Egolf, Siegrist, & Hartmann, ; Hartmann & Siegrist, ; Kauer, Pelchat, Rozin, & Zickgraf, ). These studies have shown that disgust sensitivity is positively correlated with picky eating and textural aversions in a cross sectional sample of healthy adults (Egolf et al, ; Kauer et al, ). Experimental studies have demonstrated the role of disgust in the development of conditioned food aversions in animals (e.g., Garcia, Kimeldorf, & Kelling, ), that the number of previous “disgust events” influences the development of neophobia (e.g., Miller & Holzman, ), and that disgust‐induced taste aversions can be replicated in humans (e.g., Arwas, Rolnick, & Lubow, ).…”
Section: Introductionmentioning
confidence: 99%
“…To discourage people from eating animal products, mobilizing disgust has proven to be a most effective strategy. In a quantitative study among German-speaking Swiss adults, Egolf et al (2018) found that food disgust was correlated with the rejection of certain food textures, leading to more food waste. Mobilizing disgust can also be achieved by highlighting the proximity and similarities between animals and humans, especially in the common ability to experience sensory feelings, such as suffering.…”
Section: Meat Consumption Marked By Disgust Indignation and Trustmentioning
confidence: 99%